Auditory Analysis of Segmental Phonemes in Kubeisa Iraqi Arabic with Reference to Standard English and Modern Standard Arabic - Al-dulaimi, Rawaa Saadoun Fahad Garen; Ahmed, Muslih Shwaysh (Al-Adab Journal, 2022)
In this study, a dialect of Iraqi that is spoken in the western Iraqi town of Kubeisa is examined. With regard to Standard English and Modern Standard Arabic, it does an auditory analysis for phonemes in isolation which include consonants and vowels. It has not previously given significant attention by scholars despite having a range of phonological features compared to other dialects spoken in western Iraq in particular and Iraq in general. This may be because Kubeisa is a small town located outside of metropolitan areas and is still considered a "virgin territory," necessitating analysis and research into the dialect used by its residents in relation to SE and MSA. The auditory analysis of the segmental phonemes of KIA with reference to SE and MSA was the focus of the current study’s explanatory qualitative design, which involved gathering and analyzing qualitative data. The analysis of taped content, comprising sentences and words said by KIA speakers using a tape-recording equipment, is the focus of the current work. According to Peter Roach’s idea of the segmental phonemes, which is a branch of segmental phonology, speech is broken down into phonemes (or segmental phonemes), which generally correspond to the phonetic components of the examined speech. In order to determine how this dialect differs from Modern Standard Arabic (MSA) and how it differs from the utterances chosen for examination, MSA was also consulted in this research. For this empirical study, the spontaneous speech of people who speak KIA was recorded in a natural setting. Relevant conclusions were reached based on the data analysis and findings. There are specific characteristics that set KIA apart from SE. This thesis found that speakers of KIA use CCs in middle positions of words more often than in initial or ending positions, that MSA and KIA speakers use less vowel sounds than speakers of SE.